A Review Method for Analysis of the Causes of Data Breach in the Pasca Pandemic - Andrie Yuswanto; Budi wibowo; Luqman Hafiz (Jurnal Komputer dan Elektro Sains, 2025)
The vulnerability of personal data breaches makes countries aware of the importance of regulations governing the protection of personal data Therefore, the importance of this research is to conduct a systematic review of the causes of data breaches based on the mechanism of activities carried out to answer problems and provide solutions to problems related to information security. The Systematic Literature Review (SLR) method was used to identify 283 papers in IEEE Xplore database, direct and signature digital science library based on automated search and predefined strings. Then 18 papers were selected for study based on inclusion and exclusion criteria. From the literature study, it can be concluded that the trends analyzed, data breaches are caused by user behavior that has not been educated about the dangers of data theft and awareness of information security.